2021
DOI: 10.1016/j.csbj.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between PTEN clinical phenotypes through mutation analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…We have previously shown that computational tools can be used to understand the consequences of missense mutations on protein structure, providing insight into molecular mechanisms of disease13 14 and further predicting disease outcome 15 16. Towards achieving the same aim in ALS, we initially curated a set (n = 1343) of clinically observed missense mutations across 111 genes from ALSoD8 and the literature (online supplemental table 1).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that computational tools can be used to understand the consequences of missense mutations on protein structure, providing insight into molecular mechanisms of disease13 14 and further predicting disease outcome 15 16. Towards achieving the same aim in ALS, we initially curated a set (n = 1343) of clinically observed missense mutations across 111 genes from ALSoD8 and the literature (online supplemental table 1).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Furthermore, biophysical simulations combined with structure-based modeling of residue interaction networks have also been used to reveal the functional role of mutation hotspots in molecular communication in some tumor suppressor proteins, [40] regulatory complexes including HSp90 [41], and SARS-CoV-2 Spike Protein, [42] as well as classify PTEN missense variants corresponding to cancer or autism spectrum disorder. [43][44][45] Our recent works have highlighted that biophysics-based and data-driven approaches, (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the relationship of MTR analysis to specific proteins, particularly with respect to the use of segmental intolerance analysis to predict or illuminate the linkage of proteins to human disease 2,3,11–15 . This highlights the fact that proteins containing intolerant segments are sometimes subjected to known disease mutations in other parts of the protein and, more rarely, even within the intolerant segment.…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies have explored the relationship of MTR analysis to specific proteins, particularly with respect to the use of segmental intolerance analysis to predict or illuminate the linkage of proteins to human disease. 2,3,[11][12][13][14][15] This highlights the fact that proteins containing intolerant segments are sometimes subjected to known disease mutations in other parts of the protein and, more rarely, even within the intolerant segment. The latter instance occurs when a disease mutation is observed in a patient-derived database such as ClinVar that is too rare to be seen in the sample of the global (mostly healthy) human population represented by the current gnomAD collection of sequences.…”
mentioning
confidence: 99%